University Role in Liaising Partners for Society Development: A Case Study of a University Contribution to Society Development Through the Liaising Social Partners in Ghana - Paul Wabike (Journal of Educational Issues, 2024)
Universities contribution to society development in Africa has been a subject of discussion since many countries attained independence in the 1960s. The university was seen as having a function of emancipating society from poverty and ignorance. The premise of this view was based on the university’s role in creating the ruling elite and knowledge generation and dissemination, which could help societies deal with development challenges (Sawyerr, 2004). These challenges pertained to political stability, food security, diseases and infrastructure development. The recognition that universities contribute to society development is thus not new in Africa; however, little is understood of the mechanisms these universities employ to fulfil this role. Applying social capital concepts to a case study at the University of Cape Coast (UCC) in Ghana, this article asks the following question: how do universities contribute to society development by creating social capital? UCC engagement with the Yamoransa community is analysed using a University-Community Engagement (UCE) context. Results show that university-community engagement may hold the key to producing tangible results while meeting community development challenges by creating social capital. Social capital helps build community capabilities by allowing access to knowledge circles and resources for the actors in the network. However, structural contexts in which universities operate in Africa may influence university contribution to social capital creation and its perceived benefits to society.